Adaptability of spring oat yield in the environments of the Near-Irtysh area in Omsk Province - P. N. Nikolaev; N. I. Aniskov; O. A. Yusova; I. V. Safonova (Труды по прикладной ботанике, генетике и селекции)
Background. The increasing interest in spring oats is constrained by high lability of climate factors in the local environments, which causes considerable variability of yields in different years. This situation may be changed by identifying, developing and introducing new oat cultivars. The aim of this work is to assess the adaptive potential of yield in spring oat cultivars developed at Omsk Agrarian Scientific Center in the environments of the Near-Irtysh area in Omsk Province, taking into account the most common statistical parameters. The object of the research were 9 spring oat cultivars recommended for cultivation in the region and undergoing the State Variety Trials: ‘Orion’ (reference), ‘Irtysh 13’, ‘Irtysh 21’, ‘Irtysh 23’, ‘Tarsky 2’, ‘Pamyati Bogachkova’, ‘Skakun’, ‘Fakel’ and ‘Sibirsky Gerkules’. Materials and methods. The experimental part of the work was carried out in 2011–2017 on the experimental fields of Omsk Agrarian Scientific Center located in the southern forest-steppe area. Agricultural practice used in the experiments was conventional for West Siberia. Mathematical data processing was based on the analysis of variance (ANOVA); yield adaptability, stability and plasticity parameters were calculated. Results. The most plastic (according to A. A. Gryaznov’s methodology) were the cultivars ‘Orion’, ‘Sibirsky Gerkules’, ‘Fakel’, ‘Tarsky 2’ and ‘Irtysh 21’ with indices of environmental plasticity 1.00– 1.07. According to S. A. Eberhard’s and W. A. Russell’s criteria, plasticity was identified in ‘Pamyati Bogachkova’, ‘Fakel’, ‘Sibirsky Gerkules’, ‘Irtysh 13’, ‘Irtysh 21’ and ‘Tarsky 2’ (linear regression coefficient: 1.10÷1.30). High stress resistance (according to A. A. Rossielle and J. Hemblin’s technique) was observed in ‘Irtysh 23’, ‘Skakun’ and ‘Orion’ (up to ‒3.0). Highly stable (according to S. A. Eberhard and W. A. Russell) were ‘Orion’, ‘Irtysh 21’, ‘Tarsky 2’, ‘Pamyati Bogachkova’, ‘Irtysh 13’, ‘Skakun’ and ‘Sibirsky Gerkules’ with minimal nonlinear deviations from the regression line (0.1–0.3). High compensatory capacity (according to A. A. Rossielle and J. Hemblin) was shown by ‘Tarsky 2’, ‘Irtysh 21’, ‘Pamyati Bogachkova’, ‘Fakel’ and ‘Orion’ (4.00÷4.20). The most adaptable cultivars (according to L. A. Zhivotkov) were ‘Sibirsky Gerkules’, ‘Irtysh 21’, ‘Tarsky 2’, ‘Fakel’ and ‘Orion’ (adaptability coefficient: 1.00–1.07%). The cultivars ‘Irtysh 13’, ‘Pamyati Bogachkova’, ‘Fakel’ and ‘Sibirsky Gerkules’ were identified (according to V. A. Dragavtsev) as intensive-type cultivars (multiplicative coefficient: 2.30); ‘Orion’, ‘Irtysh 21’, Tarsky 2’ and ‘Skakun’ as semi-intensive ones (2.00÷2.10); and ’Irtysh 23’ as an extensive-type cultivar (1.82). Conclusion. In compliance with the principle of variety ranking, the cultivars ‘Tarsky 2’, ‘Irtysh 21’, ‘Sibirsky Gerkules’, ‘Pamyati Bogachkova’ and ‘Fakel’ are most suitable for cultivation under local environmental conditions.